Analysis of the Duties and Responsibilities of Spare Parts Store Employees at Prima Jaya Aeknabara - Rita Karlina; Bayu Eko Broto; Daslan Simanjuntak (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the tasks and responsibilities of employees at Prima Jaya Sparepart Store in AekNabara and identify obstacles in their work implementation. This research uses a qualitative descriptive approach. Informants consisted of the store owner, sales employees, administrative staff, warehouse employees, and one customer selected through purposive sampling. Data were collected through interviews, observation, and documentation and analyzed using the Miles and Huberman model. The results show that employee tasks are divided into sales, administration, and warehouse sections that support store operations. Employee responsibility is reflected in honesty in transactions, accuracy in recording data, and cooperation in customer service. However, several obstacles were found, such as inaccurate record keeping, incomplete data, and overlapping tasks when the store becomes crowded. Therefore, clearer task distribution and the implementation of Standard Operating Procedures (SOP) are needed to improve work effectiveness.